Hepatoma of hatchery rainbaw trout - ΠΝΕΥΜΑΤΙΚΑΤΟΣ Γ.; ΠΑΠΑΔΟΠΟΥΛΟΣ Χ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The author describe, for the first time in Greece, a neoplastic disorder in the liver of hatchery rainbow trout. The disease observed in a fishery of the North part in Greece (EPIRUS). The Gross lesions of the liver tissue are extended, because of the presence of tumorous tissue, and is likely to show yellowish discoloration, possibly from bile which has been secreted by the neoplastic cells. Microscopically it may differ from the healthy liver tissue. The lobular architecture is disarranged because is diveloped a connective tissue and highly neoplastic cocciomatosis. In advanced stages the whole hepatic cells are substituted by connective cells and neoplastic tumor cells. Lipidosis is pronounced and cirrhosis also.